Visualization Methods in Business Intelligence Systems : an Overview - Dudycz, Helena (Metody wizualizacji w systemach Business Intelligence : przegląd rozwiązań, 2010)
Recently the quick obtainment of critical business information is very significant problem for managers, because executives of many enterprises decide to implement business intelligence (BI) applications. The usefulness of these systems is not decided by the amount of information to receive, but the amount and type of information which is required at the right moment. Visualization of the information or data should be considered as a one of the most important aspects of implementation of BI systems. Decision-makers also pay attention to easy-to-use and to understand visual techniques of data interpretation. In this paper, a solution of visualization information of business intelligence systems is presented. Solutions of visualization used in analytical applications of business intelligence systems arc characterized. Basic directions of conducted researches concerning the use of visualization methods in BI systems are indicated.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 104, s. 9-24
Keywords: business intelligence; visualization; information visualization; visual data exploration